Effects of hybrid, growing condition, storage time, and Pioneer 1174® silage inoculant on agronomic performance and nutritive value of whole-plant corn and grain sorghum silages - R. Suazo; R.N. Sonon; K.K. Bolsen (Kansas Agricultural Experiment Station Research Reports, 1993)
In 1989, two Pioneer corn hybrids, 3377 and 3389, were grown under irrigation and harvested at 80% milk line kernel maturity. Voluntary intakes and ADF digestibilities were similar for all hybrid, inoculant, and storage time combinations; however, DM digestibility was higher for 3377 silage than for 3389, and DM, CP, and NDF digestibilities were higher at the 50- than the 250-day storage time. The inoculant did not influence either voluntary intake or digestibility. In 1990, the same corn hybrids and DeKalb DK 42Y and Pioneer 8358 grain sorghum hybrids were grown under both irrigated and dryland conditions. Whole-plant DM contents were similar for irrigated hybrids, but dryland corns had lower DM values than sorghums. Whole-plant DM yields were higher for irrigated hybrids, and irrigated corns had higher yields than irrigated grain sorghums. Grain yields were higher for dryland grain sorghums than for dryland corns. Significant crop x growing condition x storage time interactions occurred for voluntary intake, DM, NDF, and ADF digestibilities. At 50 days, voluntary intake was higher for grain sorghums, and whole-plant DM digestibilities were similar within each crop, but grain sorghum silages had lower digestibilities than corn silages. At 50 days, voluntary intake was similar for all silages, and DM digestibility was higher for irrigated corn silages than for dryland corn silages and for all grain sorghum silages. The agronomic performances of the irrigated and dryland grain sorghums suggest that they are equivalent to dryland corn silage. Irrigated and dryland grain sorghum silages were of similar nutritive quality to the corn silages.
Keywords: Cattlemen' s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Corn; Sorghum; Silage; Hybrid; Inoculant